The arabidopsis sugar transporter (AtSTP) family: an update - Büttner, Michael (Plant biology, 2010)
The Arabidopsis sugar transporter (AtSTP) family is one of the best characterised families within the monosaccharide transporter (MST)-like genes. However, several aspects are still poorly investigated or not yet addressed experimentally, such as post-translational modifications and other factors affecting transport activity. This mini-review summarises recent advances in the AtSTP family as well as objectives for future studies.